23 Does Medicaid Cover Penile Prosthesis Surgery? A State-by-State Analysis. Issue 1 (1st April 2022) - Barnard, J; Grimaud, L; Yafi, F
ABSTRACT: Introduction: Malleable [MPP] and inflatable [IPP] penile prosthesis surgery for the management of erectile dysfunction is a reliable treatment option with high success rates and excellent patient satisfaction; however, Medicaid coverage transparency is poor leaving a knowledge gap in this population. Objective: The present study seeks to assess Medicaid coverage for MPP and IPP by state as evidenced by inclusion in publicly available physician fee schedules. Methods: State Medicaid websites were utilized to access public physician fee schedules. Individual search queries were performed for CPT codes 54400 and 54405 which represent insertion of MPP and IPP, respectively. Data were recorded for each device including the coverage status, physician fees, and the presence of clear documentation of a prior authorization requirement. Results: Medicaid physician fee schedules were accessible for 49 out of 50 US states, and 28 states reported coverage for at least one type of penile prosthesis (Figure). Two states reported coverage for MPP only, one state reported coverage for IPP only, and 24 states reported coverage for both devices. One state reported that it did not cover either device, but listed coverage for a self-contained IPP (CPT 54401) only. Mean physician reimbursement was $477.15 (290.82–$1175.50) for MPP placement and $691.76 (421.68–$1794.27) for IPP (Table 1). Eleven states documented prior authorization requirements within their fee schedules, while the remaining 17 states did not. Criteria for approval for prior authorization were not clearly stated in any fee schedule. Conclusions: Efforts to clearly document approval criteria and educate Men's Health providers on available coverage could result in a significant improvement in sexual satisfaction in the Medicaid population. Graphical representation of states offering Medicaid penile prosthetic coverage and physician reimbursement ranges are provided with comparison to Medicare rates (Figure). Limitations include heterogeneity in fee schedules, lack of prior authorization requirement details, inability to correlate to successful claims data, and the evolving nature of Medicaid coverage for the given procedures. Medicaid coverage exists for penile prosthetic surgery in 28 states, although often with significant non-transparent prior authorization criteria. Disclosure: No